Level Up Your English: Exploring the Power of Online Games in Indonesian High Schools - Suciawati, Aulia; Wanda Octaviani Putri; Yel Yel Iffatunnisa; Septi Qinqin (JADEs Journal of Academia in English Education, 2024)
This systematic literature review investigated the potential of online games to enhance English language learning among Indonesian high school students in the EFL (English as a Foreign Language) context. The review focused on research articles published between 2018 and 2023 that employed qualitative, quantitative, and experimental methodologies. From an initial pool of 103 articles, 18 were ultimately selected for analysis. The research explored four key areas: (1) the pedagogical implications of integrating online games into English language teaching, (2) the types of mobile game applications most suitable for this purpose, (3) the impact of online games on students' English language proficiency, and (4) the potential challenges associated with using online games in the classroom. The review revealed that online games can foster students' motivation, vocabulary acquisition, reading comprehension, writing skills, and grammatical understanding. However, the research also highlights the importance of teachers developing effective strategies for integrating online games into their curriculum to maximize their learning potential.